Low Error Rate Data Transmission in Cognitive Radio Networks (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Cognitive Radio (CR) has become a hopeful technology to enhance the spectrum  utilization  through spectrum sharing between licensed user (primary user) and unlicensed user (secondary user). An vital rule mandated for the development of such frameworks are to develop solutions that donâ€™t require any changes to the existing primary user (PU) infrastructure. An Orthogonal Frequency Division Multiplexing (OFDM) is typically worn advancements in present wireless communication systems which has the possibility of fulfilling the demand for cognitive radios intrinsically or with slight changes. In this paper, Space time block codes is used. The various antennas used on both ends for trustworthy data broadcast and interference nulling schemes. These codes can accomplish full broadcast diversification determined via the number of broadcast antennas. The MIMO is worn for enhancing the power of a wireless link, to determine the issue for lower BER and achieve a superior performance.